1998
DOI: 10.1046/j.1365-2222.1998.00190.x
|View full text |Cite
|
Sign up to set email alerts
|

Olive pollen allergy: searching for immunodominant T‐cell epitopes on the Ole e 1 molecule

Abstract: Our data suggest that the regions between 91 and 102 and 109-130 aminoacids on the Ole e 1 molecule are immunodominant T-cell epitopes. These epitopes are not recognized by IgE antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 40 publications
(48 reference statements)
1
36
1
Order By: Relevance
“…However, our results (Fig. 2) and the data of others (35)(36)(37) indicate that the amino acid sequence per se cannot determine the allergenicity of a protein because allergic and nonallergic people often recognize the same epitopes or regions in the molecule. One possibility to explain the Th2-deviated immune response by atopic individuals to a lipocalin allergen could be the way the allergen peptide is recognized by Th cells.…”
Section: Discussioncontrasting
confidence: 45%
“…However, our results (Fig. 2) and the data of others (35)(36)(37) indicate that the amino acid sequence per se cannot determine the allergenicity of a protein because allergic and nonallergic people often recognize the same epitopes or regions in the molecule. One possibility to explain the Th2-deviated immune response by atopic individuals to a lipocalin allergen could be the way the allergen peptide is recognized by Th cells.…”
Section: Discussioncontrasting
confidence: 45%
“…Studies using lymphoproliferation assays to map T cell antigenic determinants of Ags associated with DTH have demonstrated differences in the T cell repertoire in humans with different disease states (17)(18)(19)(20)(21). However, most studies of T cell responses to allergens have not shown significant differences in T cell repertoires between atopic and nonatopic subjects (22)(23)(24).…”
mentioning
confidence: 99%
“…Peptides 4 and 5 contained previously described T-cell epitopes of Ole e 1 (Fig 1). 14 The molecular weights of the peptides ranged from 3511.9 Da (peptide 2) to 4069.6 Da (peptide 1). Peptides 1, 2, and 3 were acidic, with calculated isoelectric points of less than 5.0, whereas peptides 4 and 5 were basic, with isoelectric points of greater than 9.0 (Table E4).…”
Section: Characterization Of Ole E 1-derived Peptidesmentioning
confidence: 99%
“…12,13 Therefore several attempts have been made to characterize IgE epitopes and T-cell epitopes of Ole e 1 for the development of a molecule-based therapeutic strategy. 7,14,15 With the aim of reducing IgE-mediated side effects during SIT, 2 approaches have thus far been pursued. One approach was based on the use of T cell-reactive Ole e 1 peptides 16 without IgE for inducing T-cell tolerance.…”
mentioning
confidence: 99%